2012
DOI: 10.4028/www.scientific.net/amr.506.294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ultrasonic Treatment on Physical Properties of Tapioca Starch

Abstract: A new processing method for the production of modified starch, high power ultrasonic treatment (400 W), was applied to native tapioca starch. The effect of processing parameters such as ultrasound amplitude (50 and 100%) and sonication time (10, 20 and 30 minutes) on the properties of the modified starches was investigated. Starch granule morphology observed by scanning electron microscopy (SEM), swelling power, solubility and powder x-ray diffractometry (PXRD) of the obtained ultrasonically treated tapioca st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 8 publications
(5 reference statements)
1
28
0
4
Order By: Relevance
“…And UPGC showed smaller collapsed granules, similar to what was reported by Manchun et al . (). These changes may be ascribed to the mechanical and/or cavitation effect of ultrasonic treatment in the process of gelatinisation (Sujka & Jamroz, ), which indicated ultrasonic treatment could cause more obvious changes to the granular structure of starch during UPGC.…”
Section: Resultsmentioning
confidence: 97%
“…And UPGC showed smaller collapsed granules, similar to what was reported by Manchun et al . (). These changes may be ascribed to the mechanical and/or cavitation effect of ultrasonic treatment in the process of gelatinisation (Sujka & Jamroz, ), which indicated ultrasonic treatment could cause more obvious changes to the granular structure of starch during UPGC.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, the SB as well SC of sonication-treated starches increased (Manchun et al, 2012). Ultrasonication may also result in cracks and pores, and impose damages to the granules of starches with different botanical origins (Amini, Razavi, & Mortazavi, 2015;Falsafi, Maghsoudlou, Aalami, Jafari, & Raeisi, 2019).…”
mentioning
confidence: 99%
“…The tapioca starch treated with ultrasound had greater swelling power and solubility values compared to the native starch, which can be associated with water absorption capacity. Due to the mechanical damage of the starch granule during the ultrasonic treatment, there is a higher water uptake and retention (Ljubić Herceg, Šubarić, Babić, & Herceg, ; Manchun et al, ).…”
Section: The Effect Of Ultrasound On Starch Propertiesmentioning
confidence: 99%
“…The solubility of the treated starch compared to the native increased with the length of exposure to the ultrasound, and the dual-frequency ultrasonic treatment achieved PV after 60 min, whereas the constant increase in exposure to ultrasonic treatment led to a decrease of transmittance (Zheng et al, 2013). Manchun et al (2012) studied the impact of ultrasound on the physical properties of tapioca starch. The morphology of the starch granules was observed through an electron microscope, whereby it was revealed that native starch has a spherical structure of 10-20 µm, whereas modified starches showed deformation and structural loss of the granule, creating a formation of a film-like structure (Manchun, Nunthanid, Limmatvapirat, & Sriamornsak, 2012).…”
Section: The Effec T Of Ultr a Sound On S Tarch Propertie Smentioning
confidence: 99%